PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT BCA FINANCE WISMA BCA PONDOK INDAH KOTA JAKARTA SELATAN - Jellita Jellita; Supardi, Yusuf (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to analyze the determinants that influence employee performance, both external factors (i.e., career development) and internal factors (i.e., work motivation). Furthermore, this study examines the role of motivation as a mediating variable in the relationship between career development and employee performance, and examines the direct and indirect effects of both factors on performance improvement. The study was conducted in several companies in the service and manufacturing sectors, each with diverse characteristics, particularly in terms of human resource management and career development strategies. The methodology used was a quantitative approach with multiple linear regression analysis techniques. Based on the test results, it was found that a structured and systematic career development program has a positive effect on work motivation, ultimately improving employee performance. The results also indicate that work motivation is an important factor strengthening the relationship between career development and employee performance. Therefore, companies need to pay attention to career development strategies, providing promotion opportunities, training, and adequate rewards to continuously improve motivation and performance. Additional testing by changing motivation indicators produced evidence consistent with the main test, thus strengthening the research results Keywords: Career Development, Motivation, Employee Performance